2019
DOI: 10.5558/tfc2019-015
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to climate change in Canadian forest management: Past, present and future

Abstract: Canadian forest management agencies have already made significant progress in addressing climate change. Adaptation measures have included undertaking research and completing assessments; implementing organizational changes; beginning to modify policy, practices, and approaches; developing tools; and providing guidance and education. Although progress to date is encouraging, forest managers recognize that adaptation is in its early stages. Suggested next steps include making further progress in adapting wildfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
(72 reference statements)
1
12
0
Order By: Relevance
“…Among the many technical, organizational, and economic adaptations found in the literature, the interviews showed that only some of them were implemented in the Vosges and Landes regions. In the two French study cases, implementation focused on technical changes fostering timber production and considered ecological processes to be instrumental features of forestry, a finding similar to what has been observed in the Swedish, Australian or Canadian forest sectors (Keskitalo et al 2016;Keenan 2017;Williamson et al 2019).…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Among the many technical, organizational, and economic adaptations found in the literature, the interviews showed that only some of them were implemented in the Vosges and Landes regions. In the two French study cases, implementation focused on technical changes fostering timber production and considered ecological processes to be instrumental features of forestry, a finding similar to what has been observed in the Swedish, Australian or Canadian forest sectors (Keskitalo et al 2016;Keenan 2017;Williamson et al 2019).…”
Section: Resultssupporting
confidence: 55%
“…Faced with the uncertainty and urgency of climate change, we argue that the time has now come to invest more time. We acknowledge the crucial role of technical changes in forestry and the need to upgrade their design at a wider spatial scale (Williamson et al 2019). However, a complementary way to adapt is to reconsider why forests are managed and not only how.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that estimates regarding future fire activities in this century are less than that of the historical (pre-industrial) recorded in many locations worldwide. It was suggested that boreal forest management is potentially utilized to re-create forest-age structures from fire-dominated pre-industrial landscapes [14].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the improvement of soil retention capacity is needed in the regions with higher vulnerability [ 36 , 52 , 53 ]. It is also critical to strengthen the monitoring and prediction of climate changes and consider the impact of climate changes in forest resource assessment, monitoring, investigation, analysis, and long-term planning [ 54 ]. In terms of environmental disturbance, the vulnerability tends to decrease, but the vulnerability risk of the southeastern marginal area is still high.…”
Section: Discussionmentioning
confidence: 99%